Interactions and intersections of gendered bodies at work, at home and at play - Segal, Marcia Texler, 1940- (Bingley, UK : Emerald, 2010)
The articles in the volume examine the intersection of gender with other characteristics in a variety of settings including factory floors and corporate offices, welfare offices, state legislatures, the armed forces, universities, social clubs and playing fields. Central themes running through several of the articles include how men and women conceive their identities and their futures and talk about and manage their work, family and leisure lives, how women view their bodies and images, and the progress women have -- or have not -- made in over-coming poverty and advancing in the corporate, legislative and military worlds. The research sites include Canada, Cuba, England, Greece, Israel, Mexico and the United States. As in previous volumes in the series, the authors employ a range of qualitative and quantitative methodologies and build on the current literature. Most of the articles have policy implications and are designed to stimulate further research. The volume is introduced with an essay by the editor and framed by an article about feminist intersectional research.
Interactions and intersections of gendered bodies at work, at home, and at play: an introduction / Marcia Texler Segal -- Living marked: tattooed women and perceptions of beauty and femininity / Desiré J.M. Anastasia -- 'Soul food': emotional abuse in childhood and the important role of food / Marjorie C. Feinson & Tamar Ben Dror -- Race, rank and gender: the determinants of sexual harassment for men and women in the military / Marla H. Kohlman -- Gender, class, and work: the complex impacts of globalization / Krista M. Brumley -- Membership in state legislatures: intersections of race, ethnicity and gender / Elizabeth Esterchild -- Gender, race, and perceived promotability among American employees / Carolyn Perrucci & Dina Banerjee -- Supply, demand and organizational processes: changes in women's share of management in United States Workplaces, 1966-2000 / Tiffany Taylor -- Experiencing gender, race, and class in real life: how low-income women of color strive for economic self-sufficiency and homeownership / Sharon M. Lindhorst Everhardt -- It's more than just job placement!: re-thinking workforce development policy to raise single mothers out of poverty / Mary Gatta -- "The very highest thing is family": male assistant professor's work/family management / Catherine Richards Solomon -- Women's leisure in Greece: fighting for 'A time of one's own' / Alexandra Koronaiou -- Does age matter in sport: differing experiences among women in rugby and martial arts / Giovanna Follo -- Slam dunk: strategic sport metaphors and the construction of masculine embodiment at work / Michele Rene Gregory -- Engendering ethnicity: femininity, masculinity, and ethnic Jewish identity / Marianne Cutler -- Young women's feminist identities: the impact of feminist stereotypes and heterosexual relationships / Alison Dahl Crossley -- Towards a feminist methodological approach to the intersection of race, class, and gender: lessons from Cuba / Anne R. Roschelle, Maura I. Toro-Morn and Elisa Facio.
Includes bibliographical references.
Description based on print version record.
Keywords: Sex role; Sex differences (Psychology); Sex discrimination; Feminist theory; Gender studies, gender groups; Sociology: work & labour; Social Science -- Gender Studies; Social Science -- Sociology -- General; Social Science -- Research